2008
DOI: 10.1590/s0102-76382008000400015
|View full text |Cite
|
Sign up to set email alerts
|

Varfarina previne obstruções venosas pós-implante de dispositivos cardíacos em pacientes de alto risco: análise parcial

Abstract: Varfarina previne obstruções venosas pós-implante de dispositivos cardíacos em pacientes de alto risco: análise parcialWarfarin prevents venous obstruction after cardiac devices implantation in high-risk patients: partial analysis Abstract Introduction: The incidence of venous thrombosis after cardiac devices implantation is high. Ventricular dysfunction and previous transvenous temporary leads ipsilaterally to the permanent implantation are independent risk factors. The effect of prophylactic strategies to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
1
2
0
2
Order By: Relevance
“…It could be suggested that the difference in vein thrombosis incidence for temporary vs. permanent pacemakers implanted using transfemoral access is due to early mobilization: all patients in our series were mobile on the day after implantation of a permanent pacemaker, and there were no cases of clinical thrombosis in our patients during the 20 years of follow-up. The use of oral anticoagulants in 28 (44%) of our patients also might have helped to reduce the number of thrombotic episodes, as previously reported for upper access implantation 27 .…”
Section: Discussionsupporting
confidence: 67%
“…It could be suggested that the difference in vein thrombosis incidence for temporary vs. permanent pacemakers implanted using transfemoral access is due to early mobilization: all patients in our series were mobile on the day after implantation of a permanent pacemaker, and there were no cases of clinical thrombosis in our patients during the 20 years of follow-up. The use of oral anticoagulants in 28 (44%) of our patients also might have helped to reduce the number of thrombotic episodes, as previously reported for upper access implantation 27 .…”
Section: Discussionsupporting
confidence: 67%
“…The last‐mentioned was likely to be the case, considering the fact that the patient was still very physically active until right before the syncope episodes and no other iatrogenic risk factors were present. A previous report had suggested the safety and benefit of 6‐month warfarin prophylaxis to prevent venous obstruction in high‐risk patients undergoing device implantations . Considering SVC patency, we set our eyes on the right jugular vein as the candidate to insert the ventricular pacemaker lead.…”
Section: Discussionmentioning
confidence: 99%
“…A heparina, substância natural encontrada abundantemente nas vísceras de suínos e bovinos, é utilizada desde a década de 1930 na terapia anticoagulante, sendo apontada como um dos principais avanços terapêuticos que almejam a redução da mortalidade e incapacidade física, pois sua utilização visa minimizar os efeitos adversos decorrentes das doenças cerebrovasculares (hemorragia, lesões cutâneas e trombocitopenia) e, consequentemente, reduzir sua morbi-mortalidade 1 .…”
Section: Introductionunclassified